Musculoskeletal Conditions in the Health Personnel of the Comprehensive Area of COVID-19 - Melba Esperanza Narváez Jaramillo; Cinthya Lizeth Pantoja Narváez; Julio Rodrigo Morillo Cano; Olga Mireya Alonzo Pico (Medisur)
Background: musculoskeletal disorders are a frequent pathology that affects health personnel who care for patients with COVID-19. Objective: to identify the main musculoskeletal conditions presented by health personnel in a comprehensive area of COVID-19. Method: a descriptive cross-sectional study was carried out from June to December 2021. The sample corresponded to the study population and was made up of the 40 workers that make up the health personnel who work in an integral area of COVID-19 of the Luis Gabriel Dávila Hospital in the province of Carchi, Ecuador. A structured survey was applied. The variables studied were: impediment of discomfort to perform work, presence of pain, frequent position at work, application of work mechanics, type of musculoskeletal condition. The data is presented in graphs using absolute and relative frequencies. Results: 86 % said they almost never felt discomfort when doing their work, 57 % reported having discomfort that has prevented them from carrying out their work normally and the same percentage reported almost always feeling pain in the neck, shoulder, back, arms and hands. 43 % recognized that the discomfort felt is a consequence of their workday. The combination of sitting and standing in the workplace predominated. 50 % apply labor mechanics within their work. Low back pain turned out to be the most prevalent musculoskeletal condition. Conclusions: in health personnel, musculoskeletal conditions or pain caused by the incorrect use of body mechanics techniques and malpractice impair the development of work activities.